2009
DOI: 10.1038/emboj.2009.55
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of NF-κB action by Set9-mediated lysine methylation of the RelA subunit

Abstract: Proper regulation of NF‐κB activity is critical to maintain and balance the inflammatory response. Inactivation of the NF‐κB complex relies in part on the proteasome‐mediated degradation of promoter‐bound NF‐κB, but the detailed molecular mechanism initiating this process remains elusive. Here, we show that the methylation of the RelA subunit of NF‐κB has an important function in this process. Lysine methyltransferase Set9 physically associates with RelA in vitro and in vivo in response to TNF‐α stimulation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
211
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(227 citation statements)
references
References 46 publications
13
211
3
Order By: Relevance
“…Two recent reports have also shown that NF-B is regulated by Set9 (19,24). In the first article, the authors show that Set9 regulates the expression of a subset of NF-B regulated genes in response to TNF␣ stimulation (19), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Two recent reports have also shown that NF-B is regulated by Set9 (19,24). In the first article, the authors show that Set9 regulates the expression of a subset of NF-B regulated genes in response to TNF␣ stimulation (19), which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 82%
“…In the second study, the authors show that Set9 methylates p65 at K315 and K316 and negatively regulates the transcriptional activity of p65 (24). The differences in the in vitro data might result from different epitope tags used in generating the recombinant p65 fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study of NFκB methylation showed that the p65 subunit is not associated with histone-modifying enzymes until it is activated [7], suggesting that this event only happens after NFκB is released from IκB. Furthermore, the work of Yang et al [24] provided important evidence that the methylation of NFκB occurs only when it is in the nucleus and can bind to DNA, as a DNA binding-deficient mutant of p65 was no longer a substrate for methylation by SET7/9. Levy et al [26] showed that methylation of p65 by SETD6 occurs on the chromatin-associated protein.…”
Section: Methylation Of Nfκb and Stat3 Takes Place After They Bind Tomentioning
confidence: 87%
“…Remarkably, the expression of the FBXL11 gene is induced in response to NFκB activation, forming a novel negative feedback loop similar to the one that involves the wellknown negative regulator IκB [23]. Yang et al [24] reported that K314 and K315 of p65 are monomethylated by SET7/9 in response to NFκB activation, an inhibitory modification that stimulates proteosome-mediated degradation of promoter-associated p65. Ea et al [25] reported that SET7/9 specifically methylates p65 at K37, and this methylation is restricted to the nucleus and regulates the promoter binding of p65.…”
Section: Lysine Methylation Of Nonhistone Proteinsmentioning
confidence: 99%